Human rights for whom? : sexual refugee applications in the 'gay capital' of Africa - Fernandes, André Prado (Gender Studies, 2018)
This research paper aims at analysing the evidentiary hurdles of sexuality-based refugee applications in Cape Town, the so-called gay capital of Africa. Amidst authorities' fear of bogus applicants, asylum-seekers fleeing homophobic persecution in their country of origin have to navigate the burden of proving to the South African state that they are 'truly' gay, despite sexuality's arguably elusive and intangible nature. Drawing from a literature review from fields as diverse as international human rights, queer and critical race theory, postcolonial feminism, and migration studies I start from a macro perspective by analysing the evolution of refugee studies and the emergence of the 'sexual refugee' within the human rights system, going on to explore the implications of such emergence for sexual minorities from the Global South. The study then brings its focus to the regional/local in order to look at the relationship between South Africa and the rest of the continent in terms of LGBT and refugee protection, at which point I trace the directions and encounters of my brief empirical research, dwell on issues of research reflexivity and positionality, and present the data collected through semi-structured interviews with three gay men from Uganda and Zimbabwe who sought asylum in Cape Town.